Neuroprotective action of Cortexin, Cerebrolysin and Actovegin in acute or chronic brain ischemia in rats. - Denis V Kurkin (Public Library of Science (PLoS), 2021)
This study was the first to compare the neuroprotective activity of Cerebrolysin®, Actovegin® and Cortexin® in rodent models of acute and chronic brain ischemia. The neuroprotective action was evaluated in animals with acute (middle cerebral artery occlusion) or chronic (common carotid artery stenosis) brain ischemia models in male rats. Cortexin® (1 or 3 mg/kg/day), Cerebrolysin® (538 or 1614 mg/kg/day) and Actovegin® (200 mg/kg/day) were administered for 10 days. To assess the neurological and motor impairments, open field test, adhesive removal test, rotarod performance test and Morris water maze test were performed. Brain damage was assessed macro- and microscopically, and antioxidant system activity was measured in brain homogenates. In separate experiments in vitro binding of Cortexin® to a wide panel of receptors was assessed, and blood-brain barrier permeability of Cortexin® was assessed in mice in vivo. Cortexin® or Cerebrolysin® and, to a lesser extent, Actovegin® improved the recovery of neurological functions, reduced the severity of sensorimotor and cognitive impairments in rats. Cortexin® reduced the size of necrosis of brain tissue in acute ischemia, improved functioning of the antioxidant system and prevented the development of severe neurodegenerative changes in chronic ischemia model. Radioactively labeled Cortexin® crossed the blood-brain barrier in mice in vivo with concentrations equal to 6-8% of concentrations found in whole blood. During in vitro binding assay Cortexin® (10 μg/ml) demonstrated high or moderate binding to AMPA-receptors (80.1%), kainate receptors (73.5%), mGluR1 (49.0%), GABAA1 (44.0%) and mGluR5 (39.7%), which means that effects observed in vivo could be related on the glutamatergic and GABAergic actions of Cortexin®. Thus, Cortexin, 1 or 3 mg/kg, or Cerebrolysin®, 538 or 1614 mg/kg, were effective in models acute and chronic brain ischemia in rats. Cortexin® contains compounds acting on AMPA, kainate, mGluR1, GABAA1 and mGluR5 receptors in vitro, and readily crosses the blood-brain barrier in mice.